Triple Oxygen Isotope Paleoaltimetry of Crystalline Rocks - Chamberlain, C. Page; Ibarra, Daniel E.; Kukla, Tyler; Methner, Katharina A.; Gao, Yuan (Frontiers in Earth Science, 2021)
Triple oxygen isotopes of hydrothermally altered minerals from crystalline rocks can be used to determine past elevations of mountain ranges. This method uses all three isotopes of oxygen (16O, 17O and 18O) to create arrays that can be extrapolated back to the meteoric water line. One advantage of this technique is that it relies only on oxygen isotopes in contrast to previous studies that use oxygen and hydrogen isotopes to determine the isotopic composition of meteoric waters. Our analysis suggests that hydrogen isotopes may exchange with ambient fluids. Triple oxygen isotopes provides an independent check on the reliability of hydrogen isotope studies.